Dynamometric measuring procedures for horizontal bar and uneven bars - Knoll, Kl.; Krug, J.
Based on the principle of electric strain measurement and intruding an optimal number of strain ganges accurate dynamometers for the horizontal bar and the uneven bars have been developed. Different strain forces and non-linear calibration graphes have been taken into account. Both dynamomenters have been used already at World- an European championships with confirmation of the FIG and UEG (Knoll, Krug & Wagner 1993). The measurements unit with the dynamometers in connection with synchronised video recordings are suitabled excellent for the technique training including feedback information. This based on the fast provision of the information. The measured reaction forces are the basic for the design engineer optimizing the gymnastic apparatuses. The reaction forces and the torques based on the hand friction are used for validation of the mathematical-physical models for simulation of the movements (Auspurg 1989, Arampatzis 1995, Knauf 1985). Compared with kinemetric procedures (details of the bar of 3D-procedures) the measurement of the dynamic of the horizontal or uneven bar is much more exact.